Advances in ERP-Integrated Logistics Management for Reducing Delivery Delays and Enhancing Project Delivery - Gbenga Omoegun; Joyce Efekpogua Fiemotongha; Julius Olatunde Omisola; Odira Kingsley Okenwa; Osazee Onaghinor (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The increasing complexity and globalization of supply chains have necessitated more efficient logistics operations to mitigate delivery delays and enhance overall project performance. This paper presents a systematic review of advances in Enterprise Resource Planning (ERP)-integrated logistics management systems and their role in reducing delivery delays and improving project delivery outcomes. ERP systems serve as centralized platforms that streamline data flow and enable real-time decision-making across various business functions. When integrated with logistics management, ERP solutions offer end-to-end visibility, automation of procurement and inventory processes, improved demand forecasting, and enhanced coordination among stakeholders. Recent technological developments, including cloud computing, Internet of Things (IoT), artificial intelligence (AI), and blockchain, have further augmented ERP capabilities in logistics. These technologies enable predictive analytics, automated tracking, and enhanced transparency, which are critical in identifying potential disruptions early and taking preemptive actions. The review identifies key ERP modules such as materials management, warehouse management, transportation planning, and supplier relationship management as pivotal in synchronizing logistics activities. Empirical studies analyzed in this review report significant reductions in lead times, improved adherence to delivery schedules, cost savings, and increased customer satisfaction as outcomes of ERP-integrated logistics implementations. Furthermore, the research underscores the role of ERP systems in facilitating agile responses to dynamic market conditions and disruptions, such as those experienced during the COVID-19 pandemic. Challenges such as high implementation costs, user resistance, and data integration complexities are acknowledged; however, best practices and success factors, including stakeholder engagement, phased implementation, and continuous training, are emphasized to mitigate these obstacles. In conclusion, ERP-integrated logistics management emerges as a transformative approach for organizations aiming to optimize their supply chains, reduce delivery delays, and enhance the timeliness and reliability of project delivery. Future research is encouraged to explore industry-specific ERP customizations and the long-term impact of emerging digital technologies on logistics performance. This review contributes to the growing body of knowledge supporting digital transformation in logistics and project management disciplines.